Partial ileal bypass reduces the production rate of low density lipoproteins in Watanabe heritable hyperlipidemic rabbits. - A F Stalenhoef; J L van Niekerk; P N Demacker; A van 't Laar (Journal of Lipid Research, 1984)
Partial ileal bypass surgery in homozygous Watanabe heritable hyperlipidemic (WHHL) rabbits resulted in a decrease of low density lipoproteins (LDL)-cholesterol from 14.2 +/- 2.4 to 7.0 +/- 1.2 mmol/l. To investigate the effect of partial ileal bypass on receptor-mediated and receptor-independent LDL catabolism, turnover studies were performed of radiolabeled native LDL and chemically modified LDL (methyl-LDL) in WHHL rabbits after partial ileal bypass, in WHHL control rabbits, and in New Zealand White (''normal'') rabbits. The plasma LDL pool in WHHL control rabbits was increased 10-fold. The receptor-mediated LDL clearance was essentially zero in WHHL rabbits, both in controls and after ileal bypass surgery; the fractional catabolic rates for total LDL were equal in both WHHL groups and were also similar to that for methyl-LDL in the normal rabbits. Seventy percent of the total LDL clearance in the normal rabbits occurred via the LDL receptor pathway. In the animals with a partial ileal bypass, the plasma LDL-protein pool was appreciably lower than in WHHL controls (41.6 +/- 5.7 vs 73.4 +/- 9.9 mg/kg, P less than 0.02). The absolute catabolic rate was almost 50% lower in the PIB group (21.4 +/- 2.0 vs 40.0 +/- 7.5 mg X kg-1 X day-1, P less than 0.02). These results indicate that the decrease of LDL after partial ileal bypass surgery in WHHL rabbits is the result of a reduced production rate of LDL.